2002
DOI: 10.1038/ncb897
|View full text |Cite
|
Sign up to set email alerts
|

Integrated activity of PDZ protein complexes regulates epithelial polarity

Abstract: Polarized cells contain numerous membrane domains, but it is unclear how the formation of these domains is coordinated to create a single integrated cell architecture. Genetic screens of Drosophila melanogaster embryos have identified three complexes, each containing one of the PDZ domain proteins--Stardust (Sdt), Bazooka (Baz) and Scribble (Scrib)--that control epithelial polarity and formation of zonula adherens. We find that these complexes can be ordered into a single regulatory hierarchy that is initiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
454
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(485 citation statements)
references
References 34 publications
26
454
1
4
Order By: Relevance
“…In addition it was recently shown that in combination with activation of oncogenes such as Ras, Raf or Notch, loss of Scribble leads to the development of invasive and metastatic epithelial neoplasias in Drosophila larvae (Brumby and Richardson, 2003;Pagliarini and Xu, 2003). While in this context Scribble serves to negatively regulate cell motility and invasion, during Drosophila development Scribble is required to positively regulate the migration of epithelial sheets during dorsal closure of the embryo (Bilder et al, 2003), implying the role of Scribble in controlling cell movement may be cell type and/or context dependent. The single human homologue of Scribble is highly concentrated at epithelial cell junctions and expression of Scribble can rescue the polarity and overgrowth defects of Drosophila scribble mutants suggesting that Scribble may function as a tumour suppressor and regulate polarity in mammalian cells (Dow et al, 2003;Navarro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition it was recently shown that in combination with activation of oncogenes such as Ras, Raf or Notch, loss of Scribble leads to the development of invasive and metastatic epithelial neoplasias in Drosophila larvae (Brumby and Richardson, 2003;Pagliarini and Xu, 2003). While in this context Scribble serves to negatively regulate cell motility and invasion, during Drosophila development Scribble is required to positively regulate the migration of epithelial sheets during dorsal closure of the embryo (Bilder et al, 2003), implying the role of Scribble in controlling cell movement may be cell type and/or context dependent. The single human homologue of Scribble is highly concentrated at epithelial cell junctions and expression of Scribble can rescue the polarity and overgrowth defects of Drosophila scribble mutants suggesting that Scribble may function as a tumour suppressor and regulate polarity in mammalian cells (Dow et al, 2003;Navarro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in Drosophila have shown a highly complex interaction of proteins that are involved in the development and control of epithelial cell polarity (Bilder et al, 2000(Bilder et al, , 2003Tanentzapf and Tepass 2003;Bilder 2004). These appear to be highly conserved in higher eukaryotes: the mammalian homologues of Dlg, Scribble and Lgl among others, have been shown to be able to complement Drosophila mutants lacking these proteins (Thomas et al, 1997;Dow et al, 2003;Grifoni et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…La protéine Scribble est localisée sur les membranes baso-latérales du coté basal des jonctions des cellules épithéliales de drosophile et contribue à délimiter les domaines apicaux et baso-latéraux et la position des jonctions cellulaires [17]. Outre son rôle dans la polarité des cellules épithéliales, Scribble est nécessaire à la différenciation des neuroblastes et au fonctionnement des synapses [4].…”
Section: Scribble : De La Drosophile à La Migration Astrocytaireunclassified